Hsp70 based gene expression biomarker shows growth stage specific genotypic diversity in Indian wheat (Triticum aestivum L.) cultivars - Hasan, Maryam; Barthakur, Sharmistha (Annals of Agricultural Research, 2014)
Terminal stress in wheat during grain filling period is a major issue which negatively affects growth, yield and grain quality, causing tremendous economic losses in many wheat growing regions of the world. Abiotic stress tolerance is a complex phenomenon and controlled by multiple defense genes including heat shock proteins and heat shock factors. The 70 Kd heat shock protein (Hsp70), is a molecular chaperone expressed during an intriguing array of developmental processes in plants and involved in preserving cellular functions under adverse environmental conditions. We have carried out an extensive growth stage specific expression profiling of a wheat Hsp70 gene under rainfed field conditions in generative stages and under high temperature stress in seedling stage in ten diverse cultivars. The differential induction indicates an important role for Hsp70 and potential application as gene expression biomarker in identifying phenophasic and developmental stage specific vulnerability in contrasting genotypes. The Hsp70 gene expression biomarker will also be useful tool for identifying and validating wheat cultivars and germplasm collections for early and terminal stress tolerance trait.